An optimal and secure watermarking system using SWT-SVD and PSO - Madhu B; Ganga Holi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Digital Watermarking is the efficient way introduced to authenticate ownership of digital information. In a watermarking system, a logo is inserted to identify the ownership to digital information. The proposed system uses the SWT with SVD to embed the watermark image. To enhance robustness of the proposed system PSO is adapted for the selection of optimal coefficients. PSNR and CC are the two performance parameters considered to evaluate the system.